Prevalence of insufficient weight loss 5 years after Roux-en-Y gastric bypass: metabolic consequences and prediction estimates: a prospective registry study - Andrew Beamish (BMJ Open, 2021)
Objective: The study aimed to investigate the heterogeneity of weight loss 5 years after Roux-en-Y gastric bypass (RYGB) and the association with cardiometabolic health as well as to model prediction estimates of surgical treatment failure. Design: Retrospective analysis of prospectively collected data from the Scandinavian Obesity Surgery Registry (SOReg). Setting: 29 surgical units from the whole of Sweden contributed data. Inclusion was restricted to surgical units with a retention rate of >60% five years postsurgery. Participants: 10 633 patients were extracted from SOReg. In total 5936 participants were included in the final sample, 79.1% females. The mean age of participants before surgery was 39.4±9 years and mean body mass index (BMI) 42.9±5.1. 2322 were excluded (death before the 5-year follow-up (n=148), other types of surgery or reoperations (n=637), age at surgery <18 or >55 years (n=1329), presurgery BMI <35 kg/m2 (n=208)). In total, 2375 (29%) of eligible individuals were lost to the 5-year follow-up. Main outcome: The occurrence of surgical treatment failure 5 years after surgery was based on the three previously published definitions: per cent excess BMI loss <50%, total weight loss <20% or BMI >35 where initial BMI was <50, or >40 where initial BMI was >50. In addition, we report the association between surgical treatment failure and biochemical markers of obesity-related comorbidity. We also developed predictive models to identify patients with a high risk of surgical treatment failure 5 years postsurgery. Results: In total, 23.1% met at least one definition of surgical treatment failure at year 5 which was associated with (adjusted OR) with 95% CI): type 2 diabetes (T2D, OR 2.1; 95% CI 1.6 to 2.7), dyslipidaemia (OR 1.8; 95% CI 1.6 to 2.1) and hypertension (OR 1.9; 95% CI 1.6 to 2.2). Surgical treatment failure at 5 years was predicted by combined demographic and anthropometric measures from baseline, 1 and 2 years postsurgery (area under the curve=0.874). Conclusion: Laparoscopic RYGB leads to a marked and sustained weight loss with improvement of obesity-related comorbidity in most patients. However, 23% met at least one definition of surgical treatment failure, which was associated with a greater risk of relapse and a higher incidence of T2D, dyslipidaemia and hypertension 5 years after surgery. Poor initial weight loss and early weight regain are strong predictors of long-term treatment failure and may be used for early identification of patients who require additional weight loss support.